Spatiotemporal impact of the COVID-19 pandemic lockdown on air quality pattern in Nanjing, China - Fei, Sun; Wagan, Raja Asif; Hasnain, Ahmad; Hussain, Aamir; Bhatti, Uzair Aslam; Elahi, Ehsan (Frontiers in Environmental Science, 2022)
In response to the COVID-19 outbreak, severe steps have been taken to control its rapid spread by countries globally. A nationwide lockdown was executed at the end of January 2020 in China, which resulted in a significant change and an improvement in air quality pattern. In this study, the objectives were to assess the spatio-temporal impact of the COVID-19 lockdown on air quality in Nanjing, China. The present article studied the six air pollutant parameters including PM10, PM2.5, SO2, NO2, CO and O3. The data were divided into six periods, P1-P3: pre-lockdown, during lockdown and after lockdown periods, P4-P6: 2017-19 (same dates of lockdown). The results reveal that during the COVID-19 control period, a significant drop and an improvement in air quality were observed. According to our findings, the PM10, PM2.5, SO2, NO2 and CO concentrations reduced by -33.03%, -35.41%, -21.26%, -39.79% and -20.65% respectively, while the concentration of O3 significantly increased by an average of 104.85% in Nanjing. From the previous three years to lockdown variations, PM10 (-40.60%), PM2.5 (-40.02%), SO2 (-54.19%) NO2 (-33.60%) and CO (23.16%) were also reduced, while O3 increased (10.83%). Moreover, compared with the COVID-19 period, the levels of PM10, SO2, NO2, CO and O3 increased by 2.84%, 28.55%, 4.68%, 16.44% and 37.36% respectively, while PM2.5 reduced by up to -14.34% after the lockdown in Nanjing. The outcomes of our study provide a roadmap for the scientific community and local administration to make policies to control air pollution.